A case study about action strategies of the PIBID (Scholarship Institutional Program for future teachers) about Geography teaching from the students’ perception (Terr@ Plural, 2022)
This paper discusses the experience gotten on PIBID (Scholarship Institutional Program for Teaching Initiation) from 2018 to January 2020 at the State School Francisco Bernardino in Juiz de Fora city, Minas Gerais. We sought to capture the perception of both the 6th-grade elementary school and freshman high school students and point out alternatives for more attractive classes that would approach their daily lives. Subsequently, it was identified clues of practical and theoretical alternatives for materials making and didactical methods that would provide dynamism to the content discussed in the 6th-grade classes. The main notes for more attractivity were the thematic closer to the students’ daily lives; better exposure of social and natural phenomena of the environment they live in; more extracurricular (outside school) activities. Some workshops were performed back in 2019 like poetry and music; “The globe in your hands”; the Landscape Geographic Game; the elaboration of the Francisco Bernardino’s School Atlas; fieldworks like a field trip to the UFJF (Federal University of Juiz de Fora) Climatological Station; and the study of the relief and its interaction with the urban area of Juiz de Fora City, using models and maps for that. It has been concluded that the elaboration of didactical activities set for geography teaching, taking as reference the school students’ interests linked to the “PIBIDians” academic knowledge, has significantly contributed to a more fluid Teaching-Learning process.
Keywords: Didatic materials and Methodologies; Teachers Initial Education; Continued Teacher Training